PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN: Studi Kasus pada CV. ARTLINE GLOBALINDO Surabaya - Elisa Hani Kurnia; Hesti Pandu Widodo; Diana Zuhroh (Jurnal Mahasiswa Manajemen dan Akuntansi, 2022)
Human resources are a very important factor in the current era of globalization. Because the success of a company is determined by the quality of its human resources. Therefore, to be able to develop, companies must implement good and efficient management. This study aims to determine the partial effect of work motivation on employee performance at CV. Artline Globalindo, the partial effect of the work environment on the performance of employees of CV. Artline Globalindo, and to determine the simultaneous effect of work motivation and work environment on employee performance at CV. Artline Globalindo. In this study using quantitative methods, with a population of all employees CV. Artline Globalindo, totaling 81 respondents. The sampling technique in this study is a probability sampling technique and a sampling method using simple random sampling. Sources of data used in this study are primary and secondary data. The analysis technique used is multiple linear regression. The results of this study based on the t-test of work motivation (X1) had a partial effect on employee performance with a significant value of 0.000 < 0.05. The work environment (X2) has a partial effect on employee performance (Y) with a significant value of 0.000 <0.05. Based on the F test with a significant value of 0.000 <0.05, which means that the work motivation variable (X1) and the work environment (X2) have a simultaneous effect on the employee performance variable (Y).